Incidence of encephalopathy and comorbidity in infants with perinatal asphyxia: a comparative prospective cohort study - Vega-del-Val, Cristina; Arnaez, Juan; Ochoa-Sangrador, Carlos; Garrido-Barbero, María; García-Alix, Alfredo (Frontiers in Pediatrics, 2024)
Background. Programs that aim to improve the detection hypoxic-ischemic encephalopathy (HIE) should establish which neonates suffering from perinatal asphyxia need to be monitored within the first 6 hours of life.Method. An observational prospective cohort study of infants with gestational age ≥ 35 weeks, and above 1800 g, were included according to their arterial cord pH value (ApH): £7.00 vs 7.01-7.10. Data was collected including obstetrical history, as well as neonatal comorbidities, including the presence of HIE, that happened within 6 hours of life. A standardized neurological exam was performed at discharge Results. There were 9537 births; 176 infants with ApH 7.01-7.10 and 117 infants with ApH ≤7.00. All 9 cases with moderate-to-severe HIE occurred among infants with ApH £ 7.00. The incidence of global and moderate-severe HIE was 3/1000 and 1/1000 births, respectively. Outcome at discharge (abnormal exam or death) showed an OR 12.03 (95%CI 1.53,94.96) in infants with ApH £7.00 compared to ApH 7.01-7.10 cohort. Ventilation support was 5.1 times (95%CI 2.87,9.03) more likely to be needed by those with cord ApH£7.00 compared to those with ApH 7.01-7.10, as well as hypoglycemia (37% vs 25%; p=0.026). In 55%, hypoglycemia occurred despite oral and/or intravenous glucose administration had been already initiated. Conclusions. Cord pH 7.00 might be a safe pH cut-off point when developing protocols to monitor infants born with acidemia in order to identify infants with moderate or severe HIE early on. There is non-negligible comorbidity in the ApH £7.00 cohort, but also in the 7.01-7.10 cohort.